Correction: Preparation and characterization of a novel drug-loaded Bi-layer scaffold for cartilage regeneration. Issue 27 (14th June 2022) - Yue, Yunqing; Xu, Peihu; Lei, Zhixin; Li, Kebi; Xu, Jingyi; Wen, Jing; Wang, Sining; Cheng, Wanting; Lin, Sihui; Huang, Zhijun; Xu, Haixing
Abstract : Correction for 'Preparation and characterization of a novel drug-loaded Bi-layer scaffold for cartilage regeneration' by Yunqing Yue et al., RSC Adv., 2022, 12, 9524–9533, ; https://doi.org/10.1039/D2RA00311B .